Pontine and extrapontine myelinolysis associated with rapid correction of hyponatremia - a review - Hanna Dominik; Wojciech Pawęska; Jan Radwański; Zuzanna Czudy; Marika Polatowska; Anna Gadomska; Justyna Kurek; Rafał Gorzyński; Michał Garstka; Justyna Molczyk-Sieńczak (Journal of Education, Health and Sport, 2023)
Pontine myelinolysis was first described in 1959 by Adams, Victor and Mancall and reported in alcoholic patients.[1]  It is characterized, above all, by acute non-inflammatory symmetrical lesion of myelin sheath and apoptosis of oligodendrocytes affecting the central part of the basis pontis.[5] Demyelination may also appear in other parts of central nervous system such as thalamus, basal nuclei and cerebellum. Involvement of the regions beyond pons is called extrapontine myelinolysis. These two manifestations- pontine and extrapontine myelinolysis are combined in one neurological entity- osmotic demyelination syndrome. Pontine and extrapontine myelinolysis are mainly caused by rapid increase in extracellular fluid osmolarity; usually in situation of iatrogenic correction of chronic hyponatremia.[7] The other causes include severe electrolyte disturbances other than hyponatremia (hypokalemia, hypophosphatemia, hypernatremia), anorexia nervosa, AIDS, acute alcoholic hepatitis, liver transplantation, Vernickes syndrome, chemotherapy, chronic renal failure. [11,12] Osmotic demyelination syndrome vary in clinical manifestations. The most common presentations include encephalopathies, pareses, dystonias. The method of choice in diagnostic process is MRI imaging. Treatment of osmotic demyelination syndrome is still in an experimental phase.